Elemental composition of algae-based supplements by energy dispersive x-ray fluorescence - Reboredo, Fernando H. (2021)
The aim of this study is to evaluate the elemental composition of fifteen algae-based supplements commonly sold in the Portuguese market, by energy dispersive X-ray fluorescence. Despite the fact that the majority of Kelp samples were a good source of iodine, the levels observed might well contribute to an excess in the human body, which can cause dysfunction of the thyroid gland. Furthermore, the presence of lead in Sea spaghetti, Arame, Hijiki and Wakame caused a considerable risk to public health vis a vis possible ingestion of a high daily dose. Regarding arsenic, great variability was observed in all the samples with concentrations equal to or above 60 μg/g in the case of Arame, KelpJ and Hijiki. Although algae mainly accumulate organic arsenic, some also contain high levels of its inorganic form, as is commonly pointed out for Hijiki. Thus, regular ingestion of these supplements must also take into account the mentioned facts. There is no doubt that these supplements are also good sources of other nutrients, but the lack of accurate regulations and control should alert consumers to avoid indiscriminate use of these types of products.